1931
DOI: 10.2307/1135784
|View full text |Cite
|
Sign up to set email alerts
|

The Basis of a Crime Index

Abstract: 5it has been suggested that there might be a possibility that private organizations such as insurance companies, commercial establishments, etc., might

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 0 publications
0
18
0
3
Order By: Relevance
“…More than 35 years later, this idea was presented in a graphic way by the President's Commission on Law Enforcement and Administration of Justice (1967: 8-9), which represented the criminal justice system as a funnel in which the number of cases decreases -because some cases are removed as they are, for example, unknown to the police or because the police, the prosecutors or the courts cannot solve them-as the process advances. 4 In order to understand the position of Sellin (1931), one must place it in its historical and geographical context, which corresponds to the period in which the Uniform Crime Reporting system (UCR) was created in the United States. One of the main decisions that had to be taken at that moment was whether to use court or police data as a basis for the UCR, which was meant to be the first comprehensive collection of criminal data at the national level.…”
Section: Historical Development Of Conviction Statisticsmentioning
confidence: 99%
See 3 more Smart Citations
“…More than 35 years later, this idea was presented in a graphic way by the President's Commission on Law Enforcement and Administration of Justice (1967: 8-9), which represented the criminal justice system as a funnel in which the number of cases decreases -because some cases are removed as they are, for example, unknown to the police or because the police, the prosecutors or the courts cannot solve them-as the process advances. 4 In order to understand the position of Sellin (1931), one must place it in its historical and geographical context, which corresponds to the period in which the Uniform Crime Reporting system (UCR) was created in the United States. One of the main decisions that had to be taken at that moment was whether to use court or police data as a basis for the UCR, which was meant to be the first comprehensive collection of criminal data at the national level.…”
Section: Historical Development Of Conviction Statisticsmentioning
confidence: 99%
“…Thus, in 1930, the national police statistics of the United States were born. Sellin (1931) published his article immediately after that, taking position in the debate about the validity of police and conviction statistics, and suggesting indirectly the way in which the future crime index elaborated on the basis of the data collected for the URC -that he mentions in page 346, note 22-could be elaborated. This can be clearly seen in the sentence that Sellin (1931) wrote immediately after the one that was going to become his dictum: "In other words, police statistics, particularly those of 'crimes known to the police' are most likely to furnish a good basis for a crime index".…”
Section: Historical Development Of Conviction Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Implied in this definition is the view that behaviours are still deemed 'criminal' even if they are not officially documented and prosecuted. Criminologists have long acknowledged the limitations of official convictions and official records in estimating criminal activity (Erickson & Empey, 1963;Sellin, 1931;Sutherland, 1934), with research showing that criminal activity is more prevalent than indicated by official conviction records (Erickson & Empey, 1963;Porterfield, 1943). To overcome these limitations researchers have implemented self-report delinquency scales to estimate the prevalence of criminal activity in the general community (Krohn, Thornberry, Gibson, & Baldwin, 2010).…”
Section: Background To Researchmentioning
confidence: 99%